2016
DOI: 10.3389/fpsyg.2016.01175
|View full text |Cite
|
Sign up to set email alerts
|

The Personality Trait of Intolerance to Uncertainty Affects Behavior in a Novel Computer-Based Conditioned Place Preference Task

Abstract: Recent work has found that personality factors that confer vulnerability to addiction can also affect learning and economic decision making. One personality trait which has been implicated in vulnerability to addiction is intolerance to uncertainty (IU), i.e., a preference for familiar over unknown (possibly better) options. In animals, the motivation to obtain drugs is often assessed through conditioned place preference (CPP), which compares preference for contexts where drug reward was previously received. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 65 publications
1
19
2
Order By: Relevance
“…Another learning task applicable to addiction in animal models is conditioned place preference in which a location is paired with a reward such as drug administration. Radell et al [ 66 ] found that high IU individuals tended to enter a more rewarding room first and concluded that IU may produce a cognitive bias that results in decision making processes which increase vulnerability to addiction.…”
Section: Discussionmentioning
confidence: 99%
“…Another learning task applicable to addiction in animal models is conditioned place preference in which a location is paired with a reward such as drug administration. Radell et al [ 66 ] found that high IU individuals tended to enter a more rewarding room first and concluded that IU may produce a cognitive bias that results in decision making processes which increase vulnerability to addiction.…”
Section: Discussionmentioning
confidence: 99%
“…As highlighted by others [5, 6, 9], virtual reality CPP tasks provide the opportunity to assess the brain substrates involved in conditioned reward. Importantly, this task could also be used to assess the effects of pharmacological treatments on both the acquisition and extinction of appetitive conditioning.…”
Section: Discussionmentioning
confidence: 99%
“…Most recently, Astur and colleagues [8] extended their model to show that individuals exhibited a CPP for an environment associated with points, or secondary reinforcers with no intrinsic value. Finally, Radell et al [9] used a modified virtual reality CPP task with contingent delivery of secondary reinforcers (golden eggs) to show that individuals with a preference for familiarity over unpredictability exhibited a bias toward a room associated with a high probability of reward. Together these studies have demonstrated that it is possible to establish preferences for virtual environments associated with music, food and secondary reinforcers.…”
Section: Introductionmentioning
confidence: 99%
“…Several computer-based analogues have been developed for use in humans ( Childs & De Wit, 2009 ; Molet, Billiet & Bardo, 2013 ; Astur, Carew & Deaton, 2014 ; Childs, Astur & De Wit, 2017 ). Most relevant to the current work is a study that examined whether IU was associated with CPP in a probabilistic task where college students could forage for reward (i.e., points in the task) in two virtual rooms, one of which was associated with more frequent reward ( Radell et al, 2016 ). This study found that, when given a choice, participants with higher IU tended to return to the room previously associated with a higher chance of reward, while those with lower IU showed no such preference ( Radell et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…Most relevant to the current work is a study that examined whether IU was associated with CPP in a probabilistic task where college students could forage for reward (i.e., points in the task) in two virtual rooms, one of which was associated with more frequent reward ( Radell et al, 2016 ). This study found that, when given a choice, participants with higher IU tended to return to the room previously associated with a higher chance of reward, while those with lower IU showed no such preference ( Radell et al, 2016 ). There are multiple possible interpretations of this preference, including that it may have resulted from a tendency to choose the more certain choice, i.e., returning to a location known to contain reward in the past, or from an increased tendency to pursue reward ( Radell et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%